2001
DOI: 10.1080/02678290110074625
|View full text |Cite
|
Sign up to set email alerts
|

Nitro substitution in achiral calamitic liquid crystals

Abstract: This review examines in some detail the eOE ect of terminal and lateral nitro substitutions in achiral calamitic liquid crystals on their physico-chemical properties. The results of this study are compared with those obtained for other groups, and are rationalized in terms of existing theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 261 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Moreover, there was, as usual, no regular change of melting temperatures with the increase of the terminal alkoxy chain length ( n ). It was previously reported that the position of the lateral NO 2 group within the molecular structure also increases the melting transition temperature [ 28 ]. Their SmA stability and range also increases gradually with n .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was, as usual, no regular change of melting temperatures with the increase of the terminal alkoxy chain length ( n ). It was previously reported that the position of the lateral NO 2 group within the molecular structure also increases the melting transition temperature [ 28 ]. Their SmA stability and range also increases gradually with n .…”
Section: Resultsmentioning
confidence: 99%
“…The strong mesomeric property of the NO 2 moiety induces a positive charge on the N atom, and thus, increases the electronegativity of the group [ 17 , 18 ]. The resonance approach has been supported by dipole moment investigations [ 25 ], NMR, and the chemical electron-withdrawing character of the nitro group, which affects the measurements [ 26 , 27 , 28 ]. For the development of the mesomorphic range and mesophase stabilities of the prepared materials, an effective strategy for modification of the architectures of compounds is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…We introduced a pendant nitro group on the aromatic ring because it has been suggested that (i) LCs with a nitro group at the ortho position to a linkage ester group typically form a nematic phase with a relatively low phase transition temperature (31) and, more importantly, (ii) the introduction of a polar (e.g., nitro) or polarizable group into the chemical structure often results in an increase of molecular polarity, affecting molecular packing and, in turn, the phase stability of LCs (31). In particular, aromatic ester-based mesogens could achieve a stable nematic phase through strong intermolecular dipoledipole interactions between carbonyl groups of adjacent molecules, an effect that increases with the strength of the molecular interaction (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Because of its linear structure, such effects would be less important with the cyano group. Petrov and Shimizu [59] have shown that the introduction of a nitro group into the liquid crystalline system, in the place of the cyano group, usually leads to a decrease of the clearing temperatures and nematic ranges, but there were also cases where the same substituent increased the melting points.…”
Section: Comparison Of the Thermal Properties Of Lcsmentioning
confidence: 98%